Global burden of anemia attributable to non-communicable diseases: GBD 2021 analysis and projections - Yu, Danqing; Ni, Yulu; Chen, Kai; Xu, Haiyan; Huang, Xin; He, Yinhui (Frontiers in Nutrition, 2025)
BackgroundAnemia is a significant global health issue affecting approximately one-third of the world’s population. Non-communicable diseases (NCDs) such as diabetes, cardiovascular diseases, and chronic kidney disease are increasingly recognized as significant contributors to anemia, particularly in populations with high prevalence of these conditions.Methods and resultsGlobally, the prevalence of anemia caused by NCDs has increased significantly from 249.1 million to 368.4 million, representing a 48% increase since 1990. A similar trend can be observed in YLDs. The burden was expected to continue to grow in the next 20 years. The curves of anemia-related burden showed an intersection for different genders around the age of children under five and women of reproductive age, beyond which women exhibit a higher burden of anemia, compared to men. Populous countries like India [102.35 million (95% UI: 97.49–108.13)], and China [45.63 million (95% UI: 42.15–49.89)] have the largest number of anemia cases caused by NCDs. Hemoglobinopathies and hemolytic anemias, being the key underlying cause of anemia, accounted for 69.0% of the anemia-related burden. There is a discernible upward trend across all socio-demographic index (SDI) groups over the years, particularly in low-middle SDI countries. While age-standardized, the burden of anemia in all SDI groups has shown a decrease trend. And the highest prevalence rates and YLDs rates always appeared in low-middle and middle SDI regions, similar with that of health system grouping levels.Conclusion and interpretationOur study reveals that anemia is particularly prevalent in low- and middle-income countries, where it significantly impacts vulnerable populations such as children under five and women of reproductive age. Understanding these multifaceted influences is essential for developing targeted and effective strategies to alleviate the burden of anemia globally.